2017
DOI: 10.1186/s13054-017-1656-7
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent association of glucocorticoids with adverse outcome in community-acquired pneumonia: a 6-year prospective cohort study

Abstract: BackgroundThe hypothalamic-pituitary-adrenal stress axis plays a crucial role in community-acquired pneumonia (CAP), with high cortisol being associated with disease severity and corticosteroid treatment resulting in earlier time to recovery. Our aim in the present study was to compare different glucocorticoid hormones, including cortisol, 11-deoxycortisol, cortisone, and corticosterone, regarding their association with short- and long-term adverse outcomes in a well-defined CAP cohort.MethodsWe prospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 47 publications
0
5
0
1
Order By: Relevance
“…Blood samples of all enrolled patients were taken for routine testing with tube type BD Vacutainer Serum SST II Advance. Additionally, further serum aliquots were frozen at −80 • C and stored until tested for metabolomic markers [24][25][26][27]. As secondary tubes, conical false bottom tubes made of polyethylene with a lamellar plug were used.…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples of all enrolled patients were taken for routine testing with tube type BD Vacutainer Serum SST II Advance. Additionally, further serum aliquots were frozen at −80 • C and stored until tested for metabolomic markers [24][25][26][27]. As secondary tubes, conical false bottom tubes made of polyethylene with a lamellar plug were used.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, initial high serum levels of 17-OH-progesterone were associated with significant better long-term survival in males and in the entire cohort. 17-OH-progesterone is a precursor of the stress hormone cortisol; thus, it is likely that higher serum levels of 17-OH-progesterone reflect a more pronounced stress response with cortisol production, which has already been shown to be beneficial regarding long-term survival in CAP patients [ 8 ].We did not find these associations of dihydrotestosterone or 17-OH-progesterone with long-term mortality in females. The female population was significantly younger, had a longer life expectancy and 6-year mortality was significantly lower (38%) than in the male population (53%).…”
Section: Discussionmentioning
confidence: 99%
“…Consecutively, the adrenal gland produces a variety of glucocorticoid, mineralocorticoid and sexual hormones. Different studies have shown a correlation of cortisol levels with severity, short- and long-term outcome in CAP and sepsis [ 3 8 ]. An independent association of aldosterone levels with survival-time in septic shock in canine bacterial sepsis has also been shown [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Upon admission to the ICU, blood samples from each patient were drawn for routine chemistry measurements and additionally, serum samples were aliquoted and frozen at −80 • C until retesting for the measurement of metabolomics biomarkers [23][24][25][26]. As secondary tubes, conical false bottom tubes made of polyethylene with a lamellar plug were used.…”
Section: Methodsmentioning
confidence: 99%